The Use of E-Mail and Google Drive by Islamic Religious Education Students at Wiralodra University Indramayu for the 2023/2024 Academic Year - Muhammad Bihar Isyqi; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study is to determine the impact of using E-Mail and Google Drive among students at the Faculty of Islamic Studies, Wiralodra University, with an emphasis on technological proficiency, information management, and interaction in an educational context. This research uses a qualitative approach using observation, in-depth interviews, and content analysis via Google Forms. E-Mail and Google Drive were highlighted as significant contributors to efficient data document delivery, document storage, collaboration, and file accessibility for students. These findings underscore its role in enhancing interactions with faculty members and facilitating activity monitoring. In conclusion, the positive adoption of E-Mail and Google Drive is in line with the paradigm of technological development as a useful tool in human life.